Предмет: Алгебра,
автор: asxat2001
решить уравнение: 5x(x-3)-5(x-1)+15(x+2)(x-2)=5
Ответы
Автор ответа:
0
5х^2-15-5х+5+15(х^2-4)=5
5х^2-15-5х+5+15х^2-60=5
-5х=15-5+60+5
-5х=75
Х=-15
5х^2-15-5х+5+15х^2-60=5
-5х=15-5+60+5
-5х=75
Х=-15
Автор ответа:
0
5x²-15x-5x+5+15(х²-4)=5
5x²-20x+5+15x²-60=5
20x²-20x-60=0
x²-x-3=0
D=1-4*(-3)=13
5x²-20x+5+15x²-60=5
20x²-20x-60=0
x²-x-3=0
D=1-4*(-3)=13
Похожие вопросы
Предмет: История,
автор: lllarquisedesade
Предмет: Математика,
автор: Аноним
Предмет: Другие предметы,
автор: aanaerkibaeva
Предмет: Математика,
автор: қаракөз
Предмет: Математика,
автор: lybimush